2014
DOI: 10.5811/westjem.2013.11.18069
|View full text |Cite
|
Sign up to set email alerts
|

Staff Perceptions of an On-site Clinical Pharmacist Program in an Academic Emergency Department after One Year

Abstract: IntroductionEmergency department clinical pharmacists (EPh) serve a relatively new clinical role in emergency medicine. New EPh may still face barriers prior to working in the emergency department (ED), including staff acceptance. We aimed to assess staff perceptions of a university hospital EPh program 1 year after implementation.MethodsWe sent an electronic survey consisting of 7 multiple-choice questions, 17 5-point Likert-scale questions, and 1 free-text comment section to ED providers and nurses. The qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…Process evaluations and other research involving multiprofessional collaboration including ward-based pharmacists often make use of surveys to study the views of the involved healthcare professionals [14][15][16][17][18][19]. These survey studies report that physicians and nurses generally are satisfied with the collaboration with the pharmacists and that an increase in the quality and safety of the patients' medication treatment is perceived.…”
Section: Introductionmentioning
confidence: 99%
“…Process evaluations and other research involving multiprofessional collaboration including ward-based pharmacists often make use of surveys to study the views of the involved healthcare professionals [14][15][16][17][18][19]. These survey studies report that physicians and nurses generally are satisfied with the collaboration with the pharmacists and that an increase in the quality and safety of the patients' medication treatment is perceived.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Fairbanks et al 7 survey showed that ED physicians and nurses are overwhelmingly in favor of the presence of an EPh in the ED, frequently seek their advice, and think that an EPh improves the quality of care. A survey by Coralic et al 8 has also proven that the EPh model of practice provides valuable perceived benefit to ED providers. A more recent survey, by Splawski et al, 9 reported that an EM pharmacist is an invaluable addition to a health-care team.…”
Section: Discussionmentioning
confidence: 99%
“…The survey instrument was developed from three previous studies that assessed staff perceptions of EM pharmacists. [7][8][9] The survey has 24 questions: 5 address demographics; 3 are general perception multiple-choice questions; and 16 are EPh specific, 5-point Likert scale questions (1-strongly agree, 5-strongly disagree). The survey was distributed to the whole ED staff by e-mail through Google forms (Google Inc.) in June 2017, after it was announced during a departmental meeting.…”
Section: Methodsmentioning
confidence: 99%
“…Recent international studies substantiate the need of clinical pharmacists to be active members of the DEM medical team. In fact, the presence of clinical pharmacists has been shown to have a positive impact on the efficient functioning of the ED [6][7][8]. Clinical pharmacy consultation services can provide drug-related information to physicians, residents, students, and nurses whenever required [6,7,[9][10][11].…”
Section: David Publishingmentioning
confidence: 99%
“…In fact, the presence of clinical pharmacists has been shown to have a positive impact on the efficient functioning of the ED [6][7][8]. Clinical pharmacy consultation services can provide drug-related information to physicians, residents, students, and nurses whenever required [6,7,[9][10][11]. Consequently, the clinical pharmacist has an important role in reducing potential ADRs and assuring medication safety to the patients through identifying and preventing MEs and ensuring appropriate medication use [9,[11][12][13][14][15][16][17][18][19].…”
Section: David Publishingmentioning
confidence: 99%